2017
DOI: 10.1016/j.ijscr.2017.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral irreducible inferior shoulder dislocation: A case report

Abstract: HighlightsBilateral luxatio erecta is rare.We present a unique case in which the dislocation was irreducible.The outcome was excellent with minimal restriction of abduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…In this case, we attempted both of these procedures under general anesthesia, but they were ineffective. To date, only two case reports have presented irreducible ISD details [ 4 , 5 ]. Frank et al reported that irreducibility occurred because of direct inhibition from the aberrant (anterior) position of the axillary nerve [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this case, we attempted both of these procedures under general anesthesia, but they were ineffective. To date, only two case reports have presented irreducible ISD details [ 4 , 5 ]. Frank et al reported that irreducibility occurred because of direct inhibition from the aberrant (anterior) position of the axillary nerve [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Frank et al reported that irreducibility occurred because of direct inhibition from the aberrant (anterior) position of the axillary nerve [ 4 ]. Khedr et al stated that humeral head entrapment in a button-hole through the inferior shoulder joint capsule inhibited reduction [ 5 ]. In our case, intraoperative findings revealed that the button-hole entrapment of the humeral head by the inferior capsule caused irreducibility, while the interposition of the axillary nerve was not observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The inferior dislocations known as luxatio erecta are infrequent constituting only 0.5% of all shoulder dislocations 2 . However, bilateral inferior dislocation of the shoulder joint is rare 3 . These usually result following significant impact from forceful hyperabduction or direct axial loading in the abducted position.…”
Section: Introductionmentioning
confidence: 99%